George R. R. Martin's attempt to convey current issues to his readership in "A game of thrones". Postmodern literature in search of social awareness and change: The case of George R. R. Martin's "A game of thrones" - Tamara Jolevska Popov; Sonja V. Strezova (University American College Skopje, 2020)
In spite of the fact that one might be fooled into thinking that George R. R. Martin's A Game of Thrones medieval setting only applies to medieval topics, his faithful readers have discovered a sinister undertone to 'a winter that lasts seven years' and 'the Long Night', accentuating the timelessness of the issues of the 21st century society. It seems as if the author's message is taking a U-turn from now and today, to the Middle Ages and back to today, unequivocally stressing the time-resisting applicability of the problem doted climate change. This paper gives an account of the literal and implicit references to the grim forecast of the planet's climate. The research is unique in its own right as it represents the initial findings of the first author's future doctoral thesis, and involves students as acknowledged participants in the research process, giving them the opportunity to partake in the world of academic publishing.
Keywords: 330; climate change; forecast; Long Night; a winter that lasts seven years; current issue; time